Effect of varieties and planting geometry on growth, yield and profitability of Kharif mungbean [Vigna radiata (L.) Wilezek] in southern Afghanistan - Ibrahimi, Faizrahman; Rana, K.S.; Choudhary, Anil K.; Dass, Anchal; Ehsan, Qudratullah; Noorzai, Amin Ullah (Annals of Agricultural Research, 2017)
An experiment was conducted at Tarnak Farm of Afghanistan National Agricultural Sciences andTechnology University (ANASTU), Kandahar, Afghanistan during Kharif 2015 to assess theperformance of mungbean varieties viz. Mai-2008, Mash-2008, NM-98 and local cultivar 'Kunduzy'in combination with 3 planting geometries (20×10, 30×10, and 40×10 cm) under semi-arid conditionsof Kandahar. It was revealed that mungbean varieties and planting geometries showed significantdifferences for growth, morpho-physiological and yield parameters. Mash-2008 exhibited highestseed yield (2031 kg ha–1) while Kunduzy led to lowest seed yield (1297 kg ha–1). Mash-2008 yielded7.8, 33 and 56% higher than Mai-2008, NM-94 and 'Kunduzy', respectively. Planting geometry of30×10 cm exhibited higher seed yield (1898 kg ha–1) followed by 20×10 cm (1641 kg ha–1). Mash-2008produced maximum straw yield while 'Kunduzy' produced minimum straw yield. Highest gross(AFN 86665 ha–1) and net returns (AFN 67672 ha–1) and B: C ratio (4.56) were observed in Mash-2008. Among planting geometries, maximum gross and net returns and B: C ratio were observed in30×10 cm spacing followed by 20×10 cm and 40×10 cm spacing. Overall, Mash-2008 under plantinggeometry of 30×10 cm led to higher growth, crop productivity and profitability followed by Mai-2008 at 30×10 cm spacing in Kharif mungbean crop under semi-arid conditions of Afghanistan.